'Lived experiences' of the love of God according to 1 John 4: A spirituality of love - van der Merwe, Dirk G. (In die Skriflig, 2017)
This article probes to enlighten this old truth of the revelation and experience of God's love in a fresh, dynamic and different way, from the perspective of early Christian spirituality. How did the early Christians possibly experience the love of God existentially in their daily lives? Another question is, 'What did they experience when they have read this text of 1 John 4:7-21? This article looks briefly at how the author of 1 John understands the character of God which is necessary for understanding the love of God. The article continues to express how the 'love' of God (according to 1 Jn), was experienced by the Early Church through the following modes of lived faith experiences that emerged from the text and existential life situations: faith experience, relational experience and mystical experience. The article shows how the contemplative reading of sacred texts can contribute to a deeper understanding and lived faith experience of God.
free
Keywords: BIBLICAL teaching on love; CHRISTIAN spirituality; GOD; JESUS Christ – Mystical body; PRIMITIVE & early church; ca. 30-600